French Validation of the Alcohol Urge Questionnaire: Psychometric Properties and Relationship with Alcohol Dependence and Drinking Behavior. (22nd October 2020) - Constant, Aymery; Sanz, Marlene; Auffret, Manon; Naudet, Florian; Vérin, Marc; Moirand, Romain
Abstract: Aim: To validate a French translation of the Alcohol Urge Questionnaire (AUQ) that measures craving in patients with alcohol dependence. Method: All patients aged > 18 years who were hospitalized for alcohol detoxification from February to May 2019 in the alcohol unit of the Rennes university hospital were eligible. A back-translated version of the AUQ was completed at admission. Patients were interviewed at the end of the 7-day detoxification program by a trained addiction psychiatrist (MS), using tablet computed-based questionnaires assessing state craving (visual analog scale), alcohol dependence severity, drinking behavior, psychological distress and physical/mental health. The same investigator assessed relapse 1 month after discharge. Results: A total of 80 inpatients were recruited and completed questionnaires. The single factor structure of the French version of the AUQ was similar to the original questionnaire, and was supported by strong internal reliability and item-scale validity. The AUQ score correlated highly acute craving measure, but moderately scales assessing the severity of alcohol dependence, drinking behavior and mental health. Relapse 1 month after discharge was significantly related to AUQ score assessed either at baseline, or with better estimate at the end of the 7-day detoxification period. Conclusion: The French version of the AUQ provides a reliable measure of phasic craving, which is best described as a context-dependent single-factor variable, related to but distinct from tonic craving, dependence severity and drinking behavior. The ease of administration makes the AUQ a useful tool for French-speaking patients with alcohol dependence. Abstract : Short Summary: We examined the psychometric properties of the French version of the Alcohol Urges Questionnaire in 80 patients entering a detoxification program in the Rennes University Hospital. This questionnaire provides a reliable measure of phasic craving, a context-dependent single-factor variable related to but distinct from dependence severity and drinking behavior.